"The Identity Dimension and the Dialogue of Cultures in the Algerian School Textbook: The Arabic Language Book for Primary School Students as a Case Study" - .koussa, alawa (El Omda in Linguistics and Discourse Analysis, 2018)
In this article, we examine the identity dimension and the dialogue of cultures in the Arabic language textbook for primary school students. We focused our research and analysis on the manifestations of identity in the reading texts—both poetic and narrative—observing the presence of historical, national, religious, and cultural-heritage dimensions. We also analyzed the levels of these aspects’ presence in shaping the identity of primary school students, given the significant role that these identity-related elements play in forming the collective consciousness of the next generation.